Evaluation of mangrove species as phytoindicator for brackish water contamination / Mohd Idwan Idris, Rashidi Othman and Izawati Tukiman - Idris, Mohd Idwan; Othman, Rashidi; Tukiman, Izawati (2012)
Mangroves ecosystem has become a resource that plays a significant role in maintaining the ecological value and human settlement need. In the sense of environmental impact, mangroves currently happened to be widely exposed to elevated heavy metal loads. Heavy metal enrichments are contributed by a variety of ongoing activities such as urban development, industrial, agricultural, and shipping activities. The aim of this study is to assess three different mangrove species as phytoindicator for three types of heavy metals contaminants in brackish water bodies at 2 different localities. All of the water samples were analyzed for lead (Pb), chromium (Cr), and zinc (Zn contaminations. The results show that 3 mangrove species which are Avicennia alba, 6ypha fruticans, and Rhizophora apiculata were found effective in indicating heavy metals contaminant in that particular environment. Based on the concentrations of heavy metals in brackish water, mangrove species can be relevant indicators for the state of a mangrove area in terms of quality of environment.